University of Florida Potato Variety Trials Spotlight: ‘French Fingerling’ - Rodrick Mwatuwa; Christian Christensen; Pam Solano; Lincoln Zotarelli (EDIS)
by Rodrick Z. Mwatuwa, Christian T. Christensen, Pam Solano, and Lincoln Zotarelli http://edis.ifas.ufl.edu/hs1300